Diagnosing endometriosis before laparoscopy: radiologic tools to evaluate the disease. Issue 4 (August 2020) - Tavcar, Jovana; Loring, Megan; Movilla, Peter R.; Clark, Nisse V.
Abstract : Purpose of review: The current gold standard for diagnosing endometriosis is laparoscopy with tissue biopsy. This review presents new evidence regarding advanced imaging for more optimal clinical assessment and preoperative evaluation for endometriosis. Recent findings: A systematic approach to the imaging evaluation of endometriosis using transvaginal ultrasound and magnetic resonance imaging has been proposed by expert groups and societies. Evidence suggests that new imaging techniques improve the accuracy of clinical diagnosis and facilitate improved preoperative mapping of endometriotic lesions. Summary: The clinical diagnosis of endometriosis, including new structured imaging protocols and techniques, is paramount in an initial evaluation. If surgery is indicated, clinical examination and imaging should provide sufficient information to anticipate the extent of surgery, properly counsel the patient, and when appropriate, refer to a minimally invasive gynecologic surgery specialist or assemble a multidisciplinary team.